Estimating Glomerular Filtration Rate in Older People. (20th March 2014) - Garasto, Sabrina; Fusco, Sergio; Corica, Francesco; Rosignuolo, Maria; Marino, Antonio; Montesanto, Alberto; De Rango, Francesco; Maggio, Marcello; Mari, Vincenzo; Corsonello, Andrea; Lattanzio, Fabrizia
Abstract : We aimed at reviewing age-related changes in kidney structure and function, methods for estimating kidney function, and impact of reduced kidney function on geriatric outcomes, as well as the reliability and applicability of equations for estimating glomerular filtration rate (eGFR) in older patients. CKD is associated with different comorbidities and adverse outcomes such as disability and premature death in older populations. Creatinine clearance and other methods for estimating kidney function are not easy to apply in older subjects. Thus, an accurate and reliable method for calculating eGFR would be highly desirable for early detection and management of CKD in this vulnerable population. Equations based on serum creatinine, age, race, and gender have been widely used. However, these equations have their own limitations, and no equation seems better than the other ones in older people. New equations specifically developed for use in older populations, especially those based on serum cystatin C, hold promises. However, further studies are needed to definitely accept them as the reference method to estimate kidney function in older patients in the clinical setting.